1992
DOI: 10.2190/cpev-kwl8-lq86-8quf
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Student-Instructor Interaction on Achievement in a Dyad Computer-Based Training (CBT) Environment

Abstract: Most computer-based training (CBT) research has ignored variables other than the software itself. Yet there are other factors which can influence achievement. This study explored the impact of instructor-student interaction when students worked CBT in pairs. Compared to an earlier study in which instructor interaction positively influence achievement when students worked CBT individually, instructor interaction had no effect on achievement. Evidently, many if not all of the social functions served by the instr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…Perhaps the social functions usually performed by an instructor are performed by the CBT team partner. Instructor interaction did not have an excessively larger effect on those paired Ss without prior experience, a result reported by Stephenson (1991).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Perhaps the social functions usually performed by an instructor are performed by the CBT team partner. Instructor interaction did not have an excessively larger effect on those paired Ss without prior experience, a result reported by Stephenson (1991).…”
Section: Discussionsupporting
confidence: 54%
“…Stephenson (1991) reported that Use of Commands did not vary between Ss receiving or not receiving instructor interaction. All Ss learned the commands equally well but some used the commands better.…”
Section: Discussionmentioning
confidence: 97%
“…Komarraju et al (2010) examined various types of student-faculty interactions concluding they "can be crucial in developing students' academic self-concept and enhancing their motivation and achievement" (p. 332). This is reinforced by Stephenson (1992), who found "an increase in student-instructor interactions produces an increase in achievement" (p. 28). Komarraju et al (2010) concluded that institutions actively fostering "close and frequent contact between their students and faculty members are more likely to reap a host of [other] benefits" (p. 332).…”
Section: Factors Influencing Faculty Satisfactionmentioning
confidence: 96%
“…If there are severe constraints in a given setting, performance is less a function of individual differences and more a function of situational factors, and less predictable from measures of theoretically-relevant individual differences. Stephenson (1991) found that the instructor /facilitator interaction with the student increased his or her achievement. Jawahar (2002) found that the perception of the situational constraints negatively influenced end user performance.…”
Section: External Supportmentioning
confidence: 97%